Exercise Performance of Chronic Heart Failure Patients in the Early Period of Support by an Axial‐Flow Left Ventricular Assist Device as Destination Therapy. Issue 5 (1st October 2013) - Compostella, Leonida; Russo, Nicola; Setzu, Tiziana; Compostella, Caterina; Bellotto, Fabio
Abstract Axial‐flow left ventricular assist devices (LVADs) are increasingly used as destination therapy in end‐stage chronic heart failure (CHF), as they improve survival and quality of life. Their effect on exercise tolerance in the early phase after implantation is still unclear. The aim of this study was to evaluate the effect of LVADs on the exercise capacity of a group of CHF patients within 2 months after initiation of circulatory support. Cardiopulmonary exercise test data were collected for 26 consecutive LVAD‐implanted CHF patients within 2 months of initiation of assistance; the reference group consisted of 30 CHF patients not supported by LVAD who were evaluated after an episode of acute heart failure. Both LVAD and reference groups showed poor physical performance; LVAD patients achieved lower workload (LVAD: 36.3 ± 9.0 W, reference: 56.6 ± 18.2 W, P < 0.001) but reached a similar peak oxygen uptake (peak VO2; LVAD: 12.5 ± 3.0 mL/kg/min, reference: 13.6 ± 2.9 mL/kg/min, P = ns) and similar percentages of predicted peak VO2 (LVAD: 48.8 ± 13.9%, reference: 54.2 ± 15.3%, P = ns). While the values of the O2 uptake efficiency slope were 12% poorer in LVAD patients than in reference patients (1124.2 ± 226.3 vs. 1280.2 ± 391.1; P = ns), the kinetics of VO2 recovery after exercise were slightly better in LVAD patients (LVAD: 212.5 ± 62.5, reference: 261.1 ± 80.2 sec, P < 0.05). In the first 2 months after initiation of circulatory support, axial‐flow LVAD patients are able to sustain a low‐intensity workload; though some cardiopulmonary exercise test parameters suggest persistence of a marked physical deconditioning, their cardiorespiratory performance is similar to that of less compromised CHF patients, possibly due to positive hemodynamic effects beginning to be produced by the assist device.